Comparative System of Lexical Elements of Verbal Forms of the Modern Russian Language and their Transfer to the Uzbek Language - Abdilhomidovich, Choriyev Bakhodir; Abduvasi ugli, Rasulov Davlatmurod (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses a more in-depth study and description of the main typological differences between the grammatical categories of verbs in the Russian and Uzbek languages.